The settlement quality study based on the physical condition of the building and the socio-economic conditions of Prenggan Village Yogyakarta - Nadia, Safa Arub; Permatasari, Dewi Halimah; Kusumawardhani, Ekky Elfira; Azzahra, Intan; Putri, Ratih Fitria (EDP Sciences, 2023)
Settlements are residential areas complete with facilities and infrastructure, both environmental and public facilities. Furthermore, the quality of settlements is the level or degree of settlements which describe settlements in meeting the needs of their inhabitants. The data collection method used was a field terrestrial survey with the help of GIS tools. Settlement quality assessment was conducted by using grading on each aspect then scored, and analyzed by using descriptive statistical analysis. The identification of the quality of settlements can be done through terrestial survey. It's a survey which takes the researcher to directly do the observation with field questionnaire.This field survey was conducted through structured interviews with selected respondents. The method used in this research is a qualitative descriptive method. This method is used to describe the condition of the quality of settlements in Prenggan Village, according to the facts in the field. The results of the research show that (1) the quality of settlements can be seen from economic characteristics aspect (KEAE), accessibility aspect (AK), physical building aspects (FB), environmental sanitation aspect (SL), residential environment aspect (LH) and (2) Prenggan Village is dominated by medium-high quality settlements. © 2023 EDP Sciences. All rights reserved.